THE STUDY OF HOUSEHOLD SOLID WASTE MANAGEMENT AT RESIDENTIAL NEAR INDUSTRIAL PARK (STUDY CASE: GRAHA MATTEL RESIDENCE, CIKARANG, INDONESIA) - Virna Deodora Agostinho Amaral (Journal of Environmental Engineering and Waste Management, 2022)
Abstract. Solid  waste management problem is become a big problem that every countries face specially developing countries like Indonesia due to the population growth that increase the waste generation with a various type of composition. For the best solid waste management,the data of solid waste generation and composition are very needed so that when make a plan or design of solid waste management can meet the target and also it is important to reduce the waste at source.The objective of this research is to analyze the household waste generation rate and waste composition per day. This research also wants to find out whether knowledge, attitude and income have influence to the behavior of housewives who live in Graha Mattel residential. The Method used in this research was Quantitative where the data of household waste generation and composition was measured and analize using the SNI standard.While for the awareness, questionnaires using likert scale that have undergone validity and reliability test were distributed directly using paper and online using Google Form to 80 housewives. Data were analyzed using Multiple Linear Regression and Classical Assumptions. The result from the research shown that the average waste generation was 1.4767 kg per day with the volume 0.0078 m3 per day or 0.3 kg/person/day and the composition are 54 percent organic following by plastic 21 percent and papers 9 percent.While for the behavior, results showed that attitude have positive significant influence toward behavior while knowledge and income has no significance towards behavior of the housewives.